Female Murderers and Stigma: Coping With the “Bad Woman” Label - Binik, Oriana (International journal of offender therapy and comparative criminology, 2025)
Among the stereotypes of female delinquency, the article focuses on “bad women” par excellence, that is to say, those convicted of murder who have not benefited from the possibility of being perceived and portrayed as “victims” because of their unorthodox femininity. The aim of the study was to understand how the label of “bad woman” is incorporated into the narration of identity of five women condemned for murder; to this end, we focus on the narratives implemented in order to cope with the stigma (narrative criminology), tracing them back to their past and the traumatic experiences they lived (psychosocial criminology). Four narratives emerge: the denied stigma, the disregarded stigma, the despairing stigma and the processed stigma. Psychosocial criminology consents to “go beyond” the surface and to find a “fil rouge” that can explain the discrepancies and the contradictions found in the way of coping with the imposed label.